<An> Empirical analysis of post-contractual behaviour in public works contracts: The Czech case as a secondrary comparison with the Slovak Republic - Schmidt, Martin
Analýza postkontraktačného správania sa verejných zadávateľov na príklade Českej republiky a v porovnaní so Slovenkom.